Utility of the Full Outline of UnResponsiveness score in children with altered sensorium: A single-center prospective observational study - Musthafa, Sanifa; Kumar, Nirmal (Journal of Pediatric Critical Care, 2024)
Background: Recent studies on the Full Outline of UnResponsiveness (FOUR) score suggest that it can overcome the limitations of the Glasgow Coma Scale (GCS). Hence, this study was planned to predict the outcome of children with altered sensorium using the FOUR score and to compare it with the GCS score. Subjects and Methods: This was a single-center prospective observational study conducted in children in the age group of ≥2 months-12 years with altered sensorium included in this study. Admission GCS and FOUR scores were collected. Data were analyzed to compare the FOUR score to GCS in relation to outcome (survivors/nonsurvivors). Results: Out of 90 cases with altered sensorium, 12 expired (13.3%). The mean (standard deviation [SD]) of age (years) was 4.69 (3.72) and the maximum in the age group of 1-5 years (n = 42). The mean (SD), median (interquartile range), and range for GCS at admission for survivors versus nonsurvivors were 11.58 (1.62) versus 6.08 (1.08), 12 (11-13) versus 6 (5.75-7), and 7-17 versus 4-8, and for FOUR score, 13.51 (1.46) versus 8.67 (1.50), 13 (13-15) versus 8 (7.75-10), and 9-16 versus 7-11 were observed, P < 0.001. Admission GCS score of ≤8 (12 out of 15) and FOUR score <11 (10 out of 12) died, P < 0.001. ROC curve analysis for mortality prediction, the area under the curve for GCS (cutoff of 8) was 0.992, and for the FOUR score (cutoff of 11), 0.989 was observed, P < 0.001. Conclusions: Admission FOUR and GCS scores are comparable for the prediction of mortality in children with altered sensorium. The FOUR score of ≤11 strongly correlated with mortality.